Pengaruh Media Sosial dalam Meningkatkan Keterlibatan Penggemar terhadap Tim Olahraga - Arsyad, Acep Nasyarullah; Maulana, Ahmad; Mangawiang, Muh. Dzakwa; Nur, Hasruddin; Syarifuddin, Syarifuddin (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2026)
The proliferation of digital communication technologies has fundamentally restructured the paradigm of sports organizations' stakeholder engagement strategies. This quantitative investigation examines the influential mechanisms through which social media platforms affect fan engagement levels toward sports entities. Employing purposive sampling methodology, 80 active sports enthusiasts meeting predetermined criteria participated in structured questionnaire administration. Multiple linear regression analysis revealed that social media variables collectively explain 74.2% variance in fan engagement intensity (R2 = 0.742, F = 18.245, p < 0.000). Instagram emerged as the predominant platform demonstrating strongest influence (β = 0.412, p < 0.000), followed by YouTube (β = 0.298, p = 0.001). Content analysis identified match highlights, behind-the-scenes footage, and athlete personal narratives as primary engagement drivers, achieving mean scores exceeding 4.3 on five-point Likert scales. Conversely, commercial- promotional content exhibited negligible impact on engagement metrics. Findings underscore the imperative for sports organizations to architect content ecosystems prioritizing authenticity, emotional resonance, and participatory elements rather than conventional broadcast approaches. This research contributes empirical evidence supporting strategic reorientation of digital communication frameworks toward relationship-centric paradigms in contemporary sports marketing landscapes.